Characterization of Muskdeer Hair & Identification of Muscone using Gas Chromatography/Mass Spectrometry - Rijal, Jiwan PD; Shakya, Birendra R; Jha, Dinesh K; Shakya, Hirdaya R; Thapa, Nirajan (Scientific World, 2010)
Muscone is a precious product of Musk deer. The identification of alleged muscone in illegal trade is a demanding job for expert. Muskdeer hair characteristics were observed and GC/MS based muscone identification effective protocol was established in this study. Keywords: Illegal trade; Muskpod; Musk deer hair; Muscone identification; GC/MS. DOI: 10.3126/sw.v7i7.3829 Scientific World Vol.7(7) 2009 pp.68-70